PENGARUH GENDER TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA SMP YANG TELAH MEMPEROLEH PENDEKATAN RME - Sambas Astra, Riki Riyanto; Vilela, Anastasia; Pereira, Jerito; Zou, Shou (IKIP Siliwangi, 2022)
This study aims to find out in depth about how much influence gender has on the mathematical creative thinking ability of junior high school students who have previously received the Realistic Mathematical Education (RME) learning approach. The method in this study uses quantitative secondary data analysis methods. The data collection technique used is documentation. Documentation is taken from a thesis that has a relevant topic/title with the same purpose. While the data analysis used in this study is the Covariance Analysis test (Ancova). The Ancova test aims to see how much gender influences the ability to think creatively in mathematics, while before the Ancova test is carried out, prerequisite tests are carried out, namely the Normality test and Homogeneity Test. The results of this study indicate that there is no influence of gender on students' creative thinking abilities. The value of the R Squared Multiple Determination Coefficient obtained is 0.041, which means 4.1% of the achievement of students' creative thinking abilities is influenced by gender factors. The remaining 95.9% is influenced by other factors, one of which is the RME learning approach carried out by previous researchers. So it can be said that the gender factor does not have a major influence on the achievement of students' mathematical creative thinking skills in the mathematics learning carried out.